'We did everything we could': how employees' made sense of COVID-19 in the tourism and hospitality industry. Issue 23 (2nd December 2022) - Bichler, Bernhard Fabian; Petry, Tanja; Peters, Mike
ABSTRACT: This study locates the COVID-19 pandemic in the realm of crisis management and by applying a novel paradox and sensemaking perspective, we illustrate how tourism organizations dealt with tensions between maintaining business as usual and preparing for the uncertain in the midst of an imminent winter season. We argue that it is not so much the novelty of the COVID-19 crisis per se but the paradoxes it created that should be considered if we are to understand how the crisis management of organizations unfolded in practice. We zoom in on the ad-hoc crisis management practices of small and medium-sized enterprises which have barely been analyzed through the lens of how they handled the pandemic and address this gap from the perspective of employees on the frontline. Using 22 interviews with regular and seasonal employees as a database, we show how employees perceived organizational attempts to manage the crisis and explore the interplay between organizational responses and employees' individual sensemaking/sensegiving attempts for coping with a paradoxical situation. Our contribution emphasizes paradox recognition as a critical sensemaking outcome for navigating an extraordinary crisis situation. The implications highlight several measures for coping with crises and securing operations once they are over.